Case report: Laparoscopic-assisted distal gastrectomy for gastric cancer in a patient with situs inversus totalis - Zhu, Kaifeng; Hu, Qiang; Sun, Yuanshui (Frontiers in Surgery, 2023)
Abstract Background: Situs inversus totalis (SIT) is a rare congenital disease as a series of clinical features of the disease caused by a mirror image distribution of the viscera to the normal anatomy. Case presentation: This study aims to report a 63-year-old male SIT patient with gastric cancer with a preoperative diagnosis of stage IIB gastric cancer (cT3N0M0), who underwent a preoperative MDT discussion and an abdominal enhancement CT for visceral evaluation to ensure a successful operation. A laparoscopic-assisted distal gastrectomy including D2 lymph node dissection and Billroth I reconstruction was successfully performed. Laparoscopic radical gastric gastrectomy and D2 lymph node dissection were performed through the opposite surgical station to the conventional one, followed by digestive tract reconstruction under small incision-assisted direct vision. There was less blood loss throughout the operation, no postoperative complications, and the patient was discharged successfully 10 days after surgery. Histopathological examination showed ulcerated high-medium differentiated adenocarcinoma stage IB (PT2N0M0). There were no complications or tumor recurrence in the patient with the examination 6 months after the operation. Conclusion: surgery in a patient with gastric cancer and SIT can be safely performed by the application of 3D laparoscopyd and small incisions to assist the digestive tract reconstruction under direct vision